ABDULLA AVLONI'S SCHOOL TEXTBOOKS EDUCATIONAL DIRECTIONS AND TASKS (Archive of Conferences, 2021)
Briefly about Avloni, Avloni has been working for more than 30 years. He witnessed the labor events of 1916, followed by revolutionary upheavals and national liberation struggles. In the past, he said, he had “left dozens of poems and school books, four theater books. When talking about its place in the history of our culture, it is necessary to emphasize two aspects: pedagogical activity and literary art. His pedagogical activity and ideas about education are important sources in defining the features of enlightenment, which reached a new level in the early twentieth century. The Avloni school was built on the basis of humanistic and free education, with the main task of teaching children secular and advanced science, and ensuring that young people have the ability to participate in the socio-political life of the country. In the article, we will witness his pedagogical activity, his educative behavior, his appeal to science, his encouragement to goodness and intelligence.